SANKSI PIDANA PELAKU TINDAK PIDANA DENGAN ANCAMAN KEKERASAN DAN TIPU MUSLIHAT MELAKUKAN PERSETUBUHAN PADA ANAK (PUTUSAN NOMOR 65/PID.B/2021/PN.SBS): Criminal Sanctions Against Perpetrators of Criminal Acts with Threats of Violence and Deception Leading to Sexual Intercourse with a Child - Dhea Andini; Eriyantouw Wahid (Faculty of Law, Universitas Trisakti, 2025)
Sexual violence against children, particularly in the form of forced sexual intercourse, is a critical issue worldwide, as perpetrators of such crimes are often individuals close to the child victim, such as family members. The identification problem discusses the legal provisions that should be applied in cases where the child is the victim and a family member is the perpetrator, as well as the appropriate sentencing measures to address similar issues. The research employs a descriptive normative approach, using secondary data which is processed qualitatively through deductive reasoning. The result and conclusion of the study indicate that the imposition of an 8-year prison sentence does not align with the objectives of criminal punishment, as there should have been an aggravated sentence with an additional one-third of the primary sentence, considering that the perpetrator had a familial relationship with the child victim.